The implications for advanced maternal age on pregnancy complications and adverse neonatal outcomes - Zeynep Gedik Özköse; Süleyman Cemil Oğlak (Perinatal Medicine Foundation, 2021)
Objective This study aimed to determine the effect of advanced maternal age (AMA) on maternal and neonatal outcomes in pregnant women aged ≥35 years compared with patients aged 30-34 years. Also, we aimed to analyze the risk estimates of potential confounders to identify whether these variables contributed to the development of adverse pregnancy outcomes or not. Methods This retrospective cohort study included 2284 pregnant women aged ≥35 years at the time of delivery who was delivered in a tertiary referral hospital from January 1, 2016, to December 31, 2020. We further classified these women into two subgroups: 35-39 years as early AMA (EAMA), and ≥40 years as very AMA (VAMA). Pregnancy complications and adverse neonatal outcomes were recorded. Results Compared to younger women, pregnant AMA women had significantly higher risks of complicated pregnancies, including a higher risk of gestational diabetes mellitus (GDM, p<0.001), polyhydramnios (p<0.001), cesarean section (p<0.001), stillbirths (p<0.001), major fetal abnormality (p<0.001), preterm delivery (p<0.001), lower birth weight (p<0.001), lower 5-minute Apgar scores (p<0.001), lower umbilical artery blood pH values (p<0.001), neonatal intensive care unit (NICU) admission (p<0.001), and length of NICU stay (p<0.001). Conclusion We found a strong and significant association between VAMA and adverse pregnancy outcomes, including an increased risk of GDM, polyhydramnios, cesarean section, and adverse neonatal outcomes, including a higher risk of stillbirths, preterm delivery, lower birth weight, lower 5-minute Apgar scores, and NICU admission.